Levels and Determinants of Prenatal Breastfeeding Knowledge, Attitude, and Intention Among Pregnant Women: A Cross-Sectional Study in Northwest Ethiopia - Chekol Abebe, Endeshaw; Ayalew Tiruneh, Gebrehiwot; Asmare Adela, Getachew; Mengie Ayele, Teklie; Tilahun Muche, Zelalem; Behaile T/Mariam, Awgichew; Tilahun Mulu, Anemut; Asmamaw Dejenie, Tadesse (Frontiers in Public Health, 2022)
Background: Pregnant women are a critical part of the community to assess various determinants of their future breastfeeding practice. This study aimed to assess the levels and determinants of breastfeeding knowledge, attitude, and intention among pregnant women. Methods: A hospital-based cross-sectional study was conducted among 422 pregnant women from January 18 to February 27, 2022, at Debre Tabor Comprehensive Specialized Hospital (DTCSH) in Northwest Ethiopia. Data were collected via face-to-face interviews from participants selected by convenience sampling technique. Data analysis was made using Stata version 16.0. Multiple logistic regression analysis was used to assess the determinants of the knowledge, attitude, and intention of pregnant women, with a p-value< 0.05 considered statistically significant. Result: About 57.8% of participants had adequate breastfeeding knowledge and only 46.9% had a positive attitude. Almost two-thirds (65.4%) of them had good intentions to breastfeed. Pregnant women attaining secondary education (AOR=2.0; 95%CI:1.31, 3.19), achieving college or university education (AOR=3.13; 95%CI: 1.63, 7.41), being multiparous (AOR =2.11; 95%CI: 1.33, 3.43), having four or more ANC visits (AOR:1.45; 95%CI:1.21, 4.31), and having prior breastfeeding experience (AOR: 3.53; 95%CI:2.22,5.65) were significant predictors of adequate knowledge. Attending college or university education (AOR=2.71;95%CI:2.33, 5.13), being multiparous(AOR=1.56; 95% CI:1.32, 8.25), and having adequate knowledge (AOR=2.02; 95% CI:1.88,7.14) were determinants of a positive breastfeeding attitude. Whereas, advanced age(AOR=1.44; 95% CI: 1.12, 5.59), adequate knowledge(AOR: 5.21; 95% CI:1.51,8.04), and positive attitude (AOR=2.41;95% CI:1.50, 4.27) were independent predictors of good breastfeeding intention. Conclusion: The breastfeeding knowledge and attitude of pregnant women were generally suboptimal. Their overall breastfeeding intention was also unsatisfactory. This highlights the need to develop culture-specific interventions aimed at improving breastfeeding knowledge, attitudes, and intention to enhance the appropriate breastfeeding practice of their future children.